Unanue - Porras Barrenechea, Raúl (1955)
To Unanue are conventional epithets incómodis and use of untrained stories. Figure Unanue and mentality of belonging to a stage and a very different environment from those of the revolution. We must agree that the explosion of revolt is the least conducive to thoughtful gathering of scholars and disciplines to develop severe patients and time.